Perikeiromene or The shorn head - Menander (Bulletin of the Institute of Classical Studies of the University of London, 2015)
Introduction. Menander and women -- The legal status of Glykera and Moschion -- The 'rape of the locks' -- Staging -- Who is Pataikos? -- The humour of Perikeiromene -- Menander's understated language -- Date -- Sources and text -- Text -- Translation -- Commentary -- Bibliography -- Index of English words -- Index of Greek words -- Index of main passages cited
Place of publication and publication date from publisher's website. - Includes bibliographical references (pages 183-191) and index. - Introduction and commentary in English; text of play in Ancient Greek and English
Keywords: Menander; Menander / Periciromene; Geschlechterverhältnis; Drama; Korinth; Griechenland